Pemerintah Responsif Pendidikan: Kajian Atas "Program Cerdas Sultraku" di Sulawesi Tenggara - Edy Karno (Shautut Tarbiyah, 2016)
Indonesian National Education System is the synergy component of the government, citizens, parents, and communities in the management of education. Nonetheless, the government appears to be the main engine of national education. This responsive attitude shown by some regional governments in Indonesia, one of the Southeast Sulawesi provincial government. The smart program sultraku derived from the vision of improving the quality of education in Southeast Sulawesi has been a major part in the development of quality human resources. This study found that the purpose of intelligent sultraku program is the improvement of human resources quality in Southeast Sulawesi. Its legal basis is Government Regulation No. 48 of 2008 on Education Funding, which is later than the regulation lowered the policy of Southeast Sulawesi Governor Regulation Number 55 Year 2014 concerning Scholarships Community Achievement Southeast Sulawesi provincial government on Sultan Agung Islamic University in Semarang, Central Java. Based on the needs analysis showed that the Regency / City in Southeast Sulawesi desperately need an education program that is responsive to local needs.Keywords: Financing Education, Quality, Policy, Programs